PENJEJAK OBJEK DENGAN BEBERAPA KAMERA MENGGUNAKAN ALGORITMA THREE STEP SEARCH - Sofwan, Aghus (TEKNIK, 2009)
In this paper we address the development of an object tracking system with multiple fixed cameras usingmotion estimation. Three step search algorithm is used to estimate object movement that across camera. Thisalgorithm will process two frame f(t-1) and f(t), where f(t-1) represents reference image, and f(t) representscurrent image at one camera to produce motion vectors value. Sequence of images that arrive from cameraswill be analyzed, then motion vectors and number of moving blocks are obtained. The motion vectors implythat object is moving to right, left, up, or down. Multiple cameras are placed as nodes in a map area havingcardinal coordinate. View direction of each camera according cardinal coordinate is whether south, east,north, or west. Based on motion vectors value and number of blocks that are moving from each camera, ouralgorithm will respond by moving the view from one camera to another, tracking objects that cross the areacovered by cameras.